Neuropsychological and behavioral disorders as presentation symptoms in two brothers with early-infantile Niemann-Pick type C: Early-infantile Niemann-Pick type C in two brothers - Soliani, Luca; Salerno, Grazia Gabriella; Pisani, Francesco; Barigazzi, Ilaria; Rizzi, Susanna; Spagnoli, Carlotta; Frattini, Daniele; Zangrandi, Andrea; Fusco, Carlo (Acta Biomedica Atenei Parmensis, 2020)
Background: Niemann-Pick disease type C (NPC) is a lysosomal storage disease caused by mutations in NPC1 or NPC2 genes. Case presentation: We present two brothers with the same compound heterozygous variants in exon 13 of the NPC1 gene (18q11.2), the first one (c.1955C> G, p. Ser652Trp), inherited from the mother, the second (c.2107T>A p.Phe703Ile) inherited from the father, associated to the classical biochemical phenotype of NPC. The two brothers presented unspecific neurologic symptoms with difference in age of onset: one presented dyspraxia and motor clumsiness at age 7 years, the other showed a systemic presentation with hepatosplenomegaly noted at the age of two months and neurological symptoms onset at age 4 with speech disturbance. Clinical evolution and neuroimaging data led to the final diagnosis. Systemic signs did not correlate with the onset of neurological symptoms. Miglustat therapy was started in both patients. Conclusions: We highlight the extreme phenotypic heterogeneity of NP-C in the presence of the same genetic variant and the unspecificity of neurologic signs at onset as previously reported. We report some positive effects of miglustat on disease progression assessed also with neuropsychological follow-up, with an age-dependent response.